Supply & installation of the metal grilles, gratings, catwalk and safety railing, rain chains and miscellaneous metal items for Brac University new campus project. - Brac University (Brac University, 2023)
This agreement made between Brac University and Labiba Engineering Foundation Supply & installation of the metal grilles, gratings, catwalk and safety railing, rain chains and miscellaneous metal items for Brac University new campus project.